2021
DOI: 10.1177/10711007211031218
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Outcomes of Percutaneous Chevron-Akin Osteotomies for the Correction of Hallux Valgus Deformity

Abstract: Background: Hallux valgus is a common cause of pain and dysfunction of the foot, sometimes requiring surgical correction when conservative measures fail. Although there are many methods of correction, one of the newer techniques is minimally invasive chevron-Akin (MICA). The aim of the current study is to evaluate clinical and radiographic effectiveness of MICA and narcotic use in a large patient cohort. Methods: All patients in this retrospective study were treated by a single fellowship-trained foot and ankl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 43 publications
1
43
1
Order By: Relevance
“…Most report high satisfaction (greater than 90%) and low complication rates. 14 , 16 , 20 , 22 The most common reason for reoperation has been for removal of hardware. 19 Rates of nonunion are variably reported, but range from 0% to 2.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most report high satisfaction (greater than 90%) and low complication rates. 14 , 16 , 20 , 22 The most common reason for reoperation has been for removal of hardware. 19 Rates of nonunion are variably reported, but range from 0% to 2.8%.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 15 , 19 , 20 Studies comparing the MIS chevron and Akin bunionectomy to open metatarsal osteotomies have generally found less pain in the early postoperative period for patients undergoing MIS surgery and no difference in clinical or radiographic outcomes between groups. 2 , 10 , 18 , 22 , 28 …”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] In a study evaluating percutaneous osteotomies for hallux valgus operation, it was reported that tourniquets were not used to prevent the development of heat necrosis. [ 21 ] In the light of this information, we think that not using a tourniquet is among the advantages of this technique.…”
Section: Discussionmentioning
confidence: 99%
“…Inherently, MIS surgery leads to less soft tissue trauma and dissection compared with open techniques and is often associated with lower levels of postoperative pain, improved wound healing, and quicker patient recovery. [12][13][14] The MIS Shannon burr in foot and ankle surgery is one component of an expanding MIS field. It may be combined with other MIS techniques such as arthroscopy and percutaneous surgery that also aim to decrease the operative insult to the delicate soft tissue envelope of the foot and ankle.…”
Section: Introductionmentioning
confidence: 99%
“…Inherently, MIS surgery leads to less soft tissue trauma and dissection compared with open techniques and is often associated with lower levels of postoperative pain, improved wound healing, and quicker patient recovery. 1214…”
Section: Introductionmentioning
confidence: 99%